Central and Peripheral Autorefraction Repeatability in Normal Eyes - Moore, Kelly E. (2014)
PURPOSE: To determine the between-visit repeatability of peripheral autorefraction measurements using the Grand Seiko WAM-5500 in normal eyes. METHODS: Cycloplegic autorefraction of the right eye was measured on 25 myopic young adults using a modified Grand Seiko autorefractor. Measurements were made centrally (along the line of sight) and ±20°, ±30°, and ±40° from the line of sight in the horizontal meridian at two visits separated by 1 to 15 days. Five autorefraction measurements at each location were converted to vector space and averaged. Relative peripheral refraction (RPR) was calculated as the difference between the peripheral and central spherical equivalent (SE). Between-visit repeatability was evaluated by plotting the difference versus the mean of the measurements at the two visits (bias) and by calculating the 95% limits of agreement (LoA). RESULTS: The mean (±SD) age and SE refractive error centrally (at visit 1) were 24.0 ± 1.3 years and −3.45 ± 1.42 D, respectively. There was no significant between-visit bias for any refractive component evaluated (M, J0, J45, and RPR) at any location measured (all p>0.05). The 95% LoA of defocus (M) was ±0.21 D centrally and increased with increasing eccentricity to ±0.73 D and ±0.88 D at 40° nasally and temporally on the retina, respectively. The 95% LoA of RPR increased with increasing eccentricity to ±0.67 D and ±0.82 D at 40° nasally and temporally on the retina, respectively. CONCLUSIONS: In normal eyes, the repeatability of cycloplegic autorefraction was best centrally and decreased as eccentricity increased; however, repeatability in the far periphery was still better than previously reported between-visit repeatability for foveal cycloplegic subjective refraction. With clear knowledge of the repeatability of on- and off-axis cycloplegic autorefraction with the Grand Seiko, peripheral measurements can be properly interpreted in longitudinal studies.